A pilot study of shortwave spectral fingerprints of smoke aerosols above liquid clouds. (December 2018) - Xu, Xiaoguang; Wang, Jun; Zeng, Jing; Hou, Weizhen; Meyer, Kerry G; Platnick, Steven E; Wilcox, Eric M
Highlights: Capability of hyperspectral measurements for retrieving properties of aerosols above water cloud is analyzed. Analytical calculation of measured radiance with respect to the principal components of smoke particle index of refraction is developed. Comparing with MODIS, hyperspectral data doubles the information for retrieving 5 additional variables Hyperspectral data provides strong constraints for qualifying radiative heating of aerosols above cloud Abstract: Absorbing aerosols like smoke heat the atmosphere by absorbing solar radiation, and such heating is enhanced when aerosols are above liquid clouds. To reduce uncertainty in estimates of the aerosol radiative forcing, it is desirable to characterize the size, index of refraction, optical depth, and altitude of smoke aerosols and underlying cloud droplets. While past work with remotely sensed multi-spectral data have made progress toward such characterization, it remains unclear if those radiatively important parameters can be fully and simultaneously retrieved from shortwave hyperspectral measurements. This issue is studied here first by examining the spectral fingerprints of above-cloud aerosols in the shortwave region (wavelength from 330 nm to 4000 nm) using hyperspectral radiative transfer simulations. These simulations are further explored to analyze the information content for hyperspectral inversion of aerosol and cloud optical depths as well as their microphysical properties over an ocean surface. The analysis shows that the Moderate Resolution Imaging Spectroradiometer (MODIS), with limited spectral bands in the solar spectrum, has partial information required for retrieving the optical depth and the effective radius of smoke and cloud. In contrast, hyperspectral measurements have about 5 extra pieces of information (double the degrees of freedom for signals of MODIS), allowing for the retrieval of additional aerosol and cloud microphysical parameters, including the smoke layer height above cloud, the imaginary part of smoke refractive index, and partially the effective variance of cloud droplet size. Thus, hyperspectral measurements can provide valuable constraints on heating rate estimates of absorbing aerosols above clouds.